Multifunctionality in molecular magnetism. (1st December 2015) - Pinkowicz, Dawid; Czarnecki, Bernard; Reczyński, Mateusz; Arczyński, Mirosław
Molecular magnetism draws from the fundamental ideas of structural chemistry and combines them with experimental physics resulting in one of the highest profile current topics, namely molecular materials that exhibit multifunctionality. Recent advances in the design of new generations of multifunctional molecular magnets that retain the functions of the building blocks and exhibit non-trivial magnetic properties at higher temperatures provide promising evidence that they may be useful for the future construction of nanoscale devices. This article is not a complete review but is rather an introduction into the fascinating world of multifunctional solids with magnetism as the leitmotif. We provide a subjective selection and discussion of the most inspiring examples of multifunctional molecular magnets: magnetic sponges, guest-responsive magnets, molecular magnets with ionic conductivity, photomagnets and non-centrosymmetric and chiral magnets.